Immunosuppression in the treatment of inflammatory bowel disease. II. The effects of azathioprine on lymphoid cell populations in a double blind trial in ulcerative colitis. - Campbell, A; Skinner, J; Maclennan, I; Hersey, P; Waller, C; Wood, J; Jewell, D; Truelove, S (1976)
Blood lymphocytes and rectal plasma cells have been studied in patients with ulcerative colitis taking part in a double-blind trial of treatment with azathioprine. Treatment for 1 year resulted in a modest fall in blood lymphocyte count, with little change in neutrophils or platelets. There was no major change in the proportions of circulating T and B lymphocytes, suggesting that the number of such cells per millilitre of blood fell in proportion to the change in lymphocyte count. The number of plasma cells in the rectal lamina propria was reduced to a mean less than half that of the control patient group. Blood K-cell cytotoxic activity fell at least 25-fold after 1 year's treatment. PHA-induced cytotoxicity was also reduced, but less consistently. Reduced K-cell activity is interpreted as reflecting depletion of effector cells from the circulation. The fall in lymphocyte count, K-cell activity and gut plasma cells was slow, indicating continuous inhibition of lymphopoiesis or differentiation throughout the trial period. Thus, azathioprine has some immunosuppressive effects which develop only after prolonged treatment. The clinical results of the trial did not show a major beneficial effect of azathioprine in the treatment of ulcerative colitis, nor were there clear correlations between the results of lymphocyte assays and clinical response in individual patients.